2019
DOI: 10.3390/app9224850
|View full text |Cite
|
Sign up to set email alerts
|

Narrow Absorption in ITO-Free Perovskite Solar Cells for Sensing Applications Analyzed through Electromagnetic Simulation

Abstract: This work reports on a computational analysis of how a modified perovskite cell can work as a refractometric sensor by generating surface plasmon resonances at its front surface. Metal-dielectric interfaces are necessary to excite plasmonic resonances. However, if the transparent conductor (ITO) is replaced by a uniform metal layer, the optical absorption at the active layer decreases significantly. This absorption enhances again when the front metallic surface is nanostructured, adding a periodic extruded arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
6
1
Order By: Relevance
“…This fact is in agreement with the physical interpretation of this peak as a selective transmitance through the slits 62 . The FOM results summarized in Table 2 are moderate compared with previously reported figures [1][2][3][4][6][7][8][9] .…”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…This fact is in agreement with the physical interpretation of this peak as a selective transmitance through the slits 62 . The FOM results summarized in Table 2 are moderate compared with previously reported figures [1][2][3][4][6][7][8][9] .…”
Section: Resultscontrasting
confidence: 56%
“…The answer includes materials and sensitized coatings to selectively detect some specimens and substances using solar cells. The published results report applications for optical sensing 1 , gas sensing 2,3 , refractive index sensing [4][5][6][7] , chemical sensing 8 , and multi-functional sensors 9 . The advantage is clear: the signal is directly generated by the solar cell and, ideally, there is no need for sophisticated and voluminous read-out elements (goniometers and spectrometer for angular and spectral interrogation techniques) [10][11][12] .…”
mentioning
confidence: 99%
“…Among them, hydrogenated amorphous silicon (aSiH) cells are commercial devices that employ an abundant, non-toxic and stable material 32 , 33 at a quite affordable price. Then, aSiH will be considered in this paper as the base device that will be transformed to work as a refractometric gas sensor interrogated opto-electronically 34 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, halide perovskites have been explored for applications as refractometric sensors, surface-enhanced Raman scattering (SERS), and biologic sensors. Elshorbagy et al theoretically reported a perovskite refractometric sensor with an extruded array of high aspect-ratio dielectric pyramids, which excited SPRs at its front surface by grating coupling with the metal surface 177 . The generated photocurrent acted as the sensing signal, where selective absorption with a spectral response narrower than 1 nm was achieved.…”
Section: Plasmonic–perovskite Sensorsmentioning
confidence: 99%